Iterative Upgrading of Small Molecular Tyrosine Kinase Inhibitors for EGFR Mutation in NSCLC: Necessity and Perspective - Jing Zhu; Qian Yang; Weiguo Xu (MDPI AG, 2021)
Molecular targeted therapy has been reported to have fewer adverse effects, and offer a more convenient route of administration, compared with conventional chemotherapy. With the development of sequencing technology, and research on the molecular biology of lung cancer, especially whole-genome information on non-small cell lung cancer (NSCLC), various therapeutic targets have been unveiled. Among the NSCLC-driving gene mutations, epidermal growth factor receptor (EGFR) mutations are the most common, and approximately 10% of Caucasian, and more than 50% of Asian, NSCLC patients have been found to have sensitive EGFR mutations. A variety of targeted therapeutic agents for EGFR mutations have been approved for clinical applications, or are undergoing clinical trials around the world. This review focuses on: the indications of approved small molecular kinase inhibitors for EGFR mutation-positive NSCLC; the mechanisms of drug resistance and the corresponding therapeutic strategies; the principles of reasonable and precision molecular structure; and the drug development discoveries of next-generation inhibitors for EGFR.